Collaborative Efforts in Transitioning from Pre-School to Elementary School for Positive Educational Foundation - Rahma Yulista Amanda; Reni Pawestuti Ambari Sumanto (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractThe teaching of calistung (reading, writing, and counting) using the drill method in early childhood schools and its use in the admission process for elementary schools present serious problems, affecting children's development and creating unhealthy competition. This study aims to describe the implementation of a fun early childhood schools to elementary schools transition movement as a solution, focusing on the roles of parents, schools, and the government, and addressing the misconception that children's success is only measured by calistung mastery. The research used qualitative methods, collecting data through interviews, observations, and documentation. Data analysis followed the Miles and Huberman model, including data reduction, presentation, and conclusion drawing. The findings reveal that the transition movement has been implemented at Semesta Bilingual School, Semarang City, Central Java despite some challenges, such as the continued use of written tests for evaluating students. Changes to the calistung test in new student admissions, a two-week period of introduction to the school environment program, and fun learning that builds six foundational skills have positively impacted students' gradual adaptation to the learning environment. Furthermore, collaboration between the government, schools, and parents through socialization, parent meetings, and active support in preparing students has been effective in enhancing student development during the transition period from early childhood schools to elementary schools, ensuring a smoother adjustment process.Keywords: transition from pre-school to elementary school, independent curriculum, positive educational foundation. AbstrakPengajaran calistung dengan metode drill di PAUD serta tes calistung dalam penerimaan siswa baru di SD merupakan masalah serius yang berdampak pada perkembangan anak dan persaingan tidak sehat. Penelitian ini bertujuan untuk menggambarkan penerapan gerakan transisi PAUD ke SD yang menyenangkan sebagai solusinya, dengan menekankan pada peran orang tua, sekolah dan pemerintah serta menghilangkan miskonsepsi bahwa keberhasilan anak hanya diukur melalui penguasaan calistung. Penelitian menggunakan metode kualitatif dengan teknik wawancara, observasi dan dokumentasi. Analisis data menggunakan model Miles dan Huberman, meliputi reduksi data, penyajian data dan penarikan kesimpulan. Temuan menunjukkan bahwa gerakan transisi telah diimplementasikan di Sekolah Semesta Bilingual, Kota Semarang, Jawa Tengah meski masih terdapat hambatan seperti dilakukannya tes tertulis sebagai evaluasi hasil belajar siswa. Perubahan tes calistung pada penerimaan siswa baru, penerapan MPLS selama dua minggu serta penerapan pembelajaran menyenangkan yang membangun enam kemampuan fondasi, memberikan dampak positif dalam penyesuaian lingkungan dan proses belajar secara bertahap selama masa transisi. Selain itu, kolaborasi antara pemerintah, lembaga pendidikan, dan orang tua melalui sosialisasi, parent meetings, dan mendukung dengan mempersiapkan siswa juga berjalan semestinya dan dapat meningkatkan perkembangan siswa selama masa transisi.Kata kunci: transisi paud ke sd, kurikulum merdeka, pondasi pendidikan positif.